Causality between urate levels with sarcopenia-related traits: a bi-directional Mendelian randomization study - Lin, Yanze; Wang, Xun; Yao, Wenchao; Sun, Yuanting; Zhou, Jinlei; Feng, Fabo (Frontiers in Endocrinology, 2023)
Background Observational studies have suggested associations between serum urate levels and sarcopenia, but the causality underlying this correlation remains uncertain. The principal objective of this study is to investigate a causal relationship of serum urate levels with sarcopenia-related traits (hand grip strength, lean mass, walking pace) using bidirectional two-sample Mendelian randomization (MR) approach. The utilization of MR methodology serves to minimize bias caused by reverse causality and confounding factors from observational studies. Methods The summary statistics of serum urate levels were derived from a cohort consisting of 288,659 individuals participating in CKDGen study. The parameters of right-hand grip strength (N=461,089), left-hand grip strength (N=461,026), appendicular lean mass (ALM) (N=450,243), whole-body lean mass(N=454,850),right-leg fat-free mass(FFM;N=454,835),left-leg FFM(N=454,805), right-arm FFM(N=454,753),left-arm FFM(N=454,672) and walking pace (N=459,915)were sourced from the UK Biobank. MR analysis was conducted utilizing inverse variance weighted (IVW), weighted median, and MR-Egger to evaluate causality. Sensitivity analysis was performed using Cochran’s Q test, MR-Egger intercept test, leave-one-out analysis and the funnel plot. Results IVW estimates demonstrated that serum urate levels exhibited no causal association with sarcopenia-related traits. In the inverse MR investigation, we had exclusively discerned an inverse correlation between walking pace and serum urate levels. No compelling evidence had surfaced to substantiate any association of other sarcopenia-related traits with serum urate. Supplemental MR methods consistently validated the findings obtained from the primary analysis. Sensitivity analysis demonstrated the robustness of findings. Conclusion Our MR study revealed the absence of the bidirectional causal relationship between serum urate levels and sarcopenia. It is imperative to acknowledge that advanced age and an individual’s health status are pivotal determinants influencing urate level and the initiation and advancement of sarcopenia. However, it is worth underscoring that these aspects remain unexamined within the purview of this study. Thus, future investigations should delve deeper into these intricate facets.